2020
DOI: 10.3390/diagnostics10121067
|View full text |Cite
|
Sign up to set email alerts
|

Dysgerminoma with a Somatic Exon 17 KIT Mutation and SHH Pathway Activation in a Girl with Turner Syndrome

Abstract: This article reports a case of a 7-year-old girl with Turner syndrome, treated with growth hormone (GH), who developed ovarian dysgerminoma. The patient karyotype was mosaic for chromosome Xq deletion: 46,X,del(X)(q22)/45,X. No Y chromosome sequences were present. Molecular studies revealed the presence of a driving mutation in exon 17 of the KIT gene in the neoplastic tissue, as well as Sonic-hedgehog (SHH) pathway activation at the protein level. The patient responded well to chemotherapy and remained in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] As examples of cases of dysgerminoma without the Y chromosome except for phenotypically normal female, dysgerminoma in Turner syndrome patients without the Y chromosome has also been reported. 36 The majority of chromosome karyotypes in Turner syndrome are 45X, X chromosome monosomy. 37 The factors related to the phenotype of Turner syndrome patients are short stature homeobox-containing gene on Xp22 38 and Xp-, Yp-homologous lymphogenic genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] As examples of cases of dysgerminoma without the Y chromosome except for phenotypically normal female, dysgerminoma in Turner syndrome patients without the Y chromosome has also been reported. 36 The majority of chromosome karyotypes in Turner syndrome are 45X, X chromosome monosomy. 37 The factors related to the phenotype of Turner syndrome patients are short stature homeobox-containing gene on Xp22 38 and Xp-, Yp-homologous lymphogenic genes.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies about the relationship between c-kit mutation and dysgerminomas have been reported. 26,30,31,36,41 It is important to accumulate case reports to further elucidate the mechanism of dysgerminoma.…”
Section: Discussionmentioning
confidence: 99%
“…Current recommendations advocate individualized and conservative approach by taking into account specific location of the gonads (scrotal or non-scrotal), the internal and external phenotype and sex of rearing 6 . GH therapy, usually implemented in women with Turner syndrome, is another risk factor of neoplasia development 7 , thus the pros and cons should be considered before going ahead with the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…About 75% dysgerminomas occur in adolescents and young adults [2] . Dysgenic gonads and sexual maldevelopment as represented by Turner syndrome, testicular feminization and triple X syndrome are supposed to be related to the occurrence of dysgerminoma [3] …”
Section: Introductionmentioning
confidence: 99%
“…[2] Dysgenic gonads and sexual maldevelopment as represented by Turner syndrome, testicular feminization and triple X syndrome are supposed to be related to the occurrence of dysgerminoma. [3] Meigs syndrome is a rare condition that manifests as an ovarian fibroma or fibroma-like tumor with ascites and pleural effusion. The hydrops usually resolves after removal of the tumor.…”
Section: Introductionmentioning
confidence: 99%